Acidity measured with the Electrical Conductivity Method (ECM) on the full EGRIP ice core, converted to hydrogen ion concentration - Sune Olander Rasmussen; Giulia Sinnl (PANGAEA, 2025)
ECM data of the East GReenland Ice core Project (EGRIP) core with the technique described by Hammer (1980) was recorded in the field during the 2017, 2018, 2019, 2022, and 2023 field seasons. The resolution of ECM data is 1 mm. The data is given as H+ ion concentration, but the absolute calibration must be considered tentative. The data set is an extension of the data presented in Mojtabavi et al., 2020, and all details regarding data processing etc. can be found therein.